The United States' Attitude towards the 1991 People's Uprising in South Kurdistan - Ismail Mohamad Hassaf; Saman Omar Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The Iraq occupation of Kuwait was a main factor for attracting the United States and approaching to the Kurds, because it radically changed US policy towards Iraq and persuated the US administration to launch a military offensive against of Iraq, which had a reflection on the Kurdish question. The first chapter examines the US position and role towards the mass uprising in South Kurdistan. The first chapter examines the US position and role towards the Kurdistan people's uprising, in the beging, the study highlighting the factors of the uprising in Kurdistan cities and towns, then the role of the US and international organizations towards the uprising. The final part will focus on the Resolution 688, and how the mass migration of Iraqi Kurds impacts on the United States and the international community to take some practical steps to protect the Kurds. It describes the deaths and victims of the Kurds, which eventually led France to draft Resolution 688 and submitted to the Security Council, as a result the Kurds being included in a UN resolution as an oppressed nation for the first time in history. At the same time, the US position for the protection and return of Kurdish refugees has been expressed.